Pengaruh Variasi Kecepatan Rotasi Spindle terhadap Gaya Potong dan Frekuensi Karakteristik Proses Bubut - Susanto, Agus; Eka Wicaksono, Ramadhana; Erik Echsony, Mohammad; Mekar Bisono, Rahayu; Widyaning Mudmainah, Putri Hana; Alfiyani, Risma (Politeknik Manufaktur Negeri Bangka Belitung, 2024)
Cutting forces analysis of turning process are one of the mandatory lecture contents given in mechanical and manufacturing department. It is because they are related to the quality of the product produced. Therefore, being able to observe and interpret cutting forces can provide an overview of machining quality of the machine. This experimental research explored the effect of spindle rotational speed on cutting process using a full octagonal shaped rings dynamometer made in the laboratory. The results showed that increasing the spindle rotation speed affected the cutting time, whether the greater the spindle rotational speed used, the faster the turning process were completed, each of which is 312.5; 156.25; and 112 seconds. However, variational of spindle rotational speed did not affect the cutting forces of turning process even though the cutting force graph showed fluctuations. Those are due to the dynamics of the machining process. Spindle rotational speed also influenced the frequency content of the process. Various characteristic frequencies of the turning process could be observed, including the spindle rotation frequency (fs) and harmonic frequencies.